Investigating Loss of Relativistic Electrons Associated With EMIC Waves at Low L Values on 22 June 2015. Issue 6 (5th June 2019) - Qin, Murong; Hudson, Mary; Li, Zhao; Millan, Robyn; Shen, Xiaochen; Shprits, Yuri; Woodger, Leslie; Jaynes, Allison; Kletzing, Craig
Abstract: In this study, rapid loss of relativistic radiation belt electrons at low L * values (2.4–3.2) during a strong geomagnetic storm on 22 June 2015 is investigated along with five possible loss mechanisms. Both the particle and wave data are obtained from the Van Allen Probes. Duskside H + band electromagnetic ion cyclotron (EMIC) waves were observed during a rapid decrease of relativistic electrons with energy above 5.2 MeV occurring outside the plasmasphere during extreme magnetopause compression. Lower He + composition and enriched O + composition are found compared to typical values assumed in other studies of cyclotron resonant scattering of relativistic electrons by EMIC waves. Quantitative analysis demonstrates that even with the existence of He + band EMIC waves, it is the H + band EMIC waves that are likely to cause the depletion at small pitch angles and strong gradients in pitch angle distributions of relativistic electrons with energy above 5.2 MeV at low L values for this event. Very low frequency wave activity at other magnetic local time can be favorable for the loss of relativistic electrons at higher pitch angles. An illustrative calculation that combines the nominal pitch angle scattering rate due to whistler mode chorus at high pitch angles with the H + band EMIC wave loss rate at low pitch angles produces loss on time scale observed at L =2.4–3.2. At high L values and lower energies, radial loss to the magnetopause is a viable explanation. Key Points: Greater than 5.2‐MeV electron loss predominantly occurs outside the plasmasphere during the extreme magnetopause compression event on 22 June 2015 Relativistic electron loss is colocated with H + band EMIC waves at low L Five possible loss mechanisms are considered to explain the fast net loss of relativistic electrons, including H + EMIC wave scattering